Effects of drought and/or high temperature stress on wild wheat relatives (AEGILOPS species) and synthetic wheats. - Pradhan, Gautam Prasad (Kansas State University, 2011)
High temperature (HT) and drought are detrimental to crop productivity, but there is limited variability for these traits among wheat ([italics]Triticum aestivum[end italics] L.) cultivars. Five [italics]Aegilops[end italics] species were screened to identify HT (52 accessions) and drought (31 accessions) tolerant species/accessions and ascertaining traits associated with tolerance. Four synthetic wheats were studied to quantify independent and combined effects of HT and drought. [italics]Aegilops[end italics] species were grown at 25/19°C day/night and 18 h photoperiod. At anthesis, HT was imposed by transferring plants to growth chambers set at 36/30°C, whereas in another experiment, drought was imposed by withholding irrigation. Synthetic wheats were grown at 21/15°C day/night and 18 h photoperiod. At anthesis or 21 d after anthesis, plants were exposed to optimum condition (irrigation + 21/15°C), HT (irrigation + 36/30°C), drought (withhold irrigation + 21/15°C), and combined stress (withhold irrigation + 36/30°C). Stresses were imposed for 16 d. High temperature and drought stress significantly decreased chlorophyll, grain number, individual grain weight, and grain yield of [italics]Aegilops[end italics] species (≥ 25%). Based on a decrease in grain yield, [italics]A. speltoides[end italics] and [italics]A. geniculata[end italics] were most tolerant (~ 61% decline), and [italics]A. longissima[end italics] was highly susceptible to HT stress (84% decline). Similarly, [italics]A. geniculata[end italics] had greater tolerance to drought (48% decline) as compared to other species (≥ 73% decline). Tolerance was associated with higher grains spike [superscript]-1 and/or heavier grains. Within [italics]A. speltoides[end italics], accession TA 2348 was most tolerant to HT with 13.5% yield decline and a heat susceptibility index (HSI) 0.23. Among [italics]A. geniculata[end italics], TA 2899 and TA 1819 were moderately tolerant to HT with an HSI 0.80. TA 10437 of [italics]A. geniculata[end italics] was the most drought tolerant accession with 7% yield decline and drought susceptibility index 0.14. Irrespective of the time of stress, HT, drought, and combined stress decreased both individual grain weight and grain yield of synthetic wheats by ≥ 37%, 26%, and 50%, respectively. These studies suggest a presence of genetic variability among [italics]Aegilops[end italics] species that can be utilized in breeding wheat for HT and drought tolerance at anthesis; and combined stress of drought and high temperature on synthetic wheats are hypo-additive in nature.
Keywords: Aegilops species; Combined stress; Drought stress; High temperature stress; Synthetic wheat; Physiology and yield traits; Agronomy (0285); Plant Sciences (0479)